Pengelolaan Sumber Daya Manusia untuk Peningkatan Kinerja Berkelanjutan di Bank Negara Infonesia - SETIAWAN, JEFRY; Kurniawati, Endah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the role of human resource management (HRM) in enhancing sustainable performance at Bank Negara Indonesia (BNI). Using a qualitative descriptive method and documentation analysis based on BNI’s 2024 Sustainability Report, the research highlights five HRM components: recruitment, training, performance appraisal, remuneration, and work-life balance. The findings show that these aspects are integrated to improve employee competence, motivation, and well-being, which in turn drive organizational resilience. The study implies that sustainable HRM practices are vital for achieving long-term economic, social, and environmental goals in the banking sector.